Atomistic modeling of a KRT35/KRT85 keratin dimer: folding in aqueous solution and unfolding under tensile load. Issue 34 (14th September 2015) - Duchstein, Patrick; Clark, Tim; Zahn, Dirk
<x xml:space="preserve">Abstract</x> We present an atomistic model of a full KRT35/KRT85 dimer, a fundamental building block of human hair.